Total Factor Productivity and its Determinants: the case of selected Coir Industries in Kerala - RASEENA K.K and K.X. Joseph
Extent and speed of industrialisation is governed by many factors and the efficiency of the activity has a major role in it. This efficiency itself is influenced by some other factors, both internal and external to the firm. The present study considers the total factor productivity as the measure of efficiency of a manufacturing firm. Here the coir industry was taken as the sourcing industry and the total factor productivity is estimated using log linear regression model under the frame work of Cobb- Douglas Production Function. Factors influencing the TFP was traced out using a multiple linear regression model and the results reveal that the factors like the average years of schooling and the pre-job and on-job training statuses of workers positively influences the TFP whereas, the method of operation and presence of the labour union were inversely affected. It was also evident from the regression result that the average age of the employees and average years of experience in manufacturing coir were not significant in influencing TFP in the Coir Industry of Kerala.